Repeated arterial chemoembolisation in a dog with an unresectable hepatocellular carcinoma. Issue 2 (14th June 2017) - Fenner, Joy; Caine, Abby; Wray, Jon; Tappin, Simon
Abstract : An 11‐year‐old male neutered Staffordshire bull terrier presented for investigation of inappetence and intermittent postprandial abdominal pain. An 8 cm diameter mass was documented within the right lateral lobe of the liver. An exploratory laparotomy was performed and removal attempted however the mass was unresectable. Biopsy confirmed a low‐grade hepatocellular carcinoma. Arterial chemoembolisation was performed and the patient discharged three days later. The mass was documented to gradually reduce in size before slowly regrowing, then to remain stable until 10 months postchemoembolisation, when the patient again became inappetent. At this time the mass was 11.5 cm diameter. Repeat chemoembolisation was performed as previously. The patient developed pancreatitis following the procedure and remained hospitalised for 10 days. Five weeks after the second procedure, the mass had reduced to 8 cm in diameter. Signs of pancreatitis returned and the dog was euthanased nine weeks after the second procedure; 14 months after the first.